PENGARUH PENDEKATAN STEM TERHADAP PENINGKATAN LITERASI SAINS SISWA SEKOLAH DASAR - Salma Ramadhani Putri; Nurdiansyah; Nenden Permas Hikmatunisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The achievement of science literacy in Indonesia is still low, based on the results of PISA in 2018 Indonesia ranks 75th out of 80 countries in the low category. Science literacy in science learning is expected that students can apply the knowledge they get at school to be used in everyday life so that students can have concern for the surrounding environment. Therefore, it takes a way of learning that can prepare students to have good learning competencies and science and technology literacy, able to think critically or problem solving, creative, communicate, and collaborate or 21st century skills. One approach that includes technology is the STEM approach. So the purpose of this study is to determine and analyze the effect of the STEM approach on improving the science literacy of elementary school students, as well as to determine and analyze the improvement of science literacy of elementary school students using the STEM approach better than students who get learning using a scientific approach. The research method used in the research is the experimental method with the type of quasi-experiment research. The research design used was nonequivalent control group design. The results of the STEM approach research findings have a significant effect on the science literacy skills of elementary school students, which is in the high category with an r square value of 0.823 or 82.3%. The improvement of science literacy skills that get learning with the STEM approach is better than students who get learning with a scientific approach. Learning with the STEM approach gets an N-Gain of 0.62 while scientific learning gets an N-Gain of 0.35, both of which fall into the medium category. Keywords: elementary school students, science literacy, STEM approach